A multifaceted, multijurisdictional, multiagency, and multidisciplinary approach to investigating unidentified and missing persons cases in Australia. (December 2022) - Ward, Jodie
Abstract: Currently, there are approximately 750 unidentified human remains and 2500 long-term missing persons in Australia. The Australian Federal Police National DNA Program for Unidentified and Missing Persons (Program) is using a multifaceted, multijurisdictional, multiagency, and multidisciplinary approach in a dedicated effort to identify these unknown deceased persons, scientifically link them to known missing persons, and provide answers to their families. The nationally coordinated Program provides its police, forensic, and coronial stakeholders with a suite of contemporary forensic technologies, databases, and experts to forensically examine the skeletonised remains and recover post-mortem data for comparison to the available ante-mortem data for each missing person. Through a number of physical and virtual public outreach activities, families with missing relatives have been encouraged to provide vital ante-mortem forensic information, records, and samples to aid the identification process. To date, this unique Program has assisted to resolve a number of unidentified and missing persons cases from both historical and contemporary contexts, using a combination of genetic and non-genetic techniques, and local and national databases. The centralisation of Program capabilities, expertise, and resources to conduct this type of unique and challenging casework is proving to be the most effective and efficient way to generate investigative leads, identify human remains, and resolve long-term missing persons cases in Australia.